Hormone therapy for premenopausal women with metastatic breast cancer: combinations with cyclin-dependent kinase inhibitors - E. V. Artamonova; E. I. Kovalenko (ABV-press, 2019)
This article discusses the problems associated with the search of the most effective treatment strategies for HER2-negative metastatic breast cancer in premenopausal women. Until recently, ovarian suppression and hormone therapy had been the main treatments used in this group of patients. The development of palbociclib, called a "breakthrough therapy", as well as promising results of trials evaluating the efficacy of cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors added to hormone therapy in postmenopausal women suggested a need for the assessment of this treatment regimen in combination with ovarian suppression in younger patients.According to the results of randomized trials and subgroup analysis, the addition of a CDK4/6 inhibitor to ovarian suppression and hormonal therapy significantly increases survival. The safety profile is similar to that of older patients. Randomized trials comparing the efficacy of palbociclib + ovarian suppression + aromatase inhibitor vs. chemotherapy in premenopausal women demonstrated significant benefits of a new treatment strategy: a CDK4/6 inhibitor as a part of combination therapy reduced the risk of progression by 36 % compared to capecitabine.